2016
DOI: 10.3389/fimmu.2016.00556
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for the Immune System in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) affects an ever-growing population of all ages with long-term consequences on health and cognition. Many of the issues that TBI patients face are thought to be mediated by the immune system. Primary brain damage that occurs at the time of injury can be exacerbated and prolonged for months or even years by chronic inflammatory processes, which can ultimately lead to secondary cell death, neurodegeneration, and long-lasting neurological impairment. Researchers have turned to rodent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
201
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(218 citation statements)
references
References 172 publications
(166 reference statements)
10
201
0
7
Order By: Relevance
“…Traumatic brain injury (TBI) is the most common cause of injury-induced death and long-term disability worldwide, especially in children and young adults (1). Approximately 10 million people sustain new TBIs each year, with an estimated overall cost of ;U.S. $406 billion (2).…”
mentioning
confidence: 99%
“…Traumatic brain injury (TBI) is the most common cause of injury-induced death and long-term disability worldwide, especially in children and young adults (1). Approximately 10 million people sustain new TBIs each year, with an estimated overall cost of ;U.S. $406 billion (2).…”
mentioning
confidence: 99%
“…The initial insult often consists of meningeal and neuronal contusion, axonal shearing and damage to blood vessels in the meninx and the brain as the ‘primary TBI’. That acutely leads to glia limitans damage, meningeal cell death, neuronal damage and the activation of glial cells such as microglia and astrocytes, which release further DAMPs and produce an inflammatory response in brain 103,104 (Fig. 4).…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…When exposed to DAMPs, phagocytic microglia are rapidly activated to clear debris (for example, a hematoma), seal defective barriers and produce neurotrophic factors 105107 . However, microglia are also critical for an extensive and often sustainable (up to years) generation of cytokines (for example, IL-1β and IL-6) and ROS, which in turn recruit neutrophils and blood monocytes-macrophages to the injured area 103,105,108 . Furthermore, complement 109 or lysophosphatidylcholine activates inflammasomes in microglia or astrocytes soon after TBI and during neuro-inflammation 110 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
See 1 more Smart Citation
“…There are also many crosseffects among this different hypotheses, which makes the pathogenesis of ischemic stroke more complex 15 . In those hypotheses, oxidative stress and inflammatory response are the most classic, which mainly refers to that a large number of oxidized and inflammatory mediators released after cerebral ischemia reperfusion, leading directly to the functional impairment, affecting the proliferation and apoptosis of neurons, aggravating cerebral ischemia reperfusion injury 16,17 . Recent studies have shown that the gene expression in ischemic stroke is abnormal, whereas HDACI can regulate the expression of genes related to neurological function through acetylation/deacetylation by histone and nonhistone, reducing the injury, promoting the revascularization of ischemic area and promoting the neuronal plasticity and functional recovery 18,19 .…”
Section: ■ Discussionmentioning
confidence: 99%